200 Evaluation of Nutrition Service Provision in a Day Hospital Setting. (16th September 2019) - Digan, Eimear; White, Sarah; Fox, Emma; Feehan, Sinead; Cronin, Audrey; Kennelly, Sean
Abstract: Background: Malnutrition, frailty and functional impairment adversely impact individuals and should be considered simultaneously in rehabilitation. Individuals in a Day Hospital (DH) setting require a multidisciplinary approach to rehabilitate and nutrition plays a fundamental role in improving patient outcomes. The aim of this study was to establish the nutritional profile of the patients attending the DH and to measure this against current dietetic referral criteria. Methods: A prospective quality improvement analysis of older adults attending the DH was conducted. Nutritional status, using the mini nutritional assessment short-form, demographic and biochemical information was collected from nursing notes and the software Key. Frailty scores were assigned using Rockwood Clinical Frailty Scale. Nutrition service provision was evaluated in relation to the priority rating system for DH Patients. Results: Nearly two-thirds of the 57 patients were malnourished (17.5%) or at risk (45.6%), 1 in 4 (26.3%) was obese. Most patients were frail (77.2%). 45.6% of patients were referred to clinical nutrition services. 90% of malnourished patients and 53.8% of those at risk were referred to dietetic services. Patients were seen at 4 ± 2.45 weeks after referral, 19.2% of patients were seen on time. Patients with underweight or obese BMI classifications were at greater risk of malnutrition and frailty. Those referred to the DH for falls review were nutritionally poorer and physically frailer. Conclusion: This study highlights the need for a focused nutritional service in this environment. Revision of dietetic referral criteria and streamlining strategies are required to provide quality, timely intervention to those who need it most.